Sri Lanka : Background Papers. (IMF Staff Country Reports; Country Report ;, 1995)
This Background Paper on Sri Lanka provides information on the economic developments during 1992-95. Developments in the domestic and external sectors are discussed. The deficiencies of the official consumer price index that resulted in a substantial understatement of inflation performance in 1994 and alternative estimates of underlying inflation are described. The structural rigidities in the labor market that perpetuate high unemployment and limit job growth are also described. The paper also examines fiscal sustainability, which emerged as the key medium-term policy objective.